Economics and education: Spending per student - Iguiñiz Echevarría, Javier (2000)
The raison d'être of education is the learning and training of students and the decisive factor in both processes is the teacher. A society concerned about what is most important must measure its achievements with indicators that express that reason for being and that decisive factor. This means showing figures, whether they are supply or demand, but always related to those two elements. What is quantified associable to the quality of education will have to be expressed largely from these figures. This quality cannot be captured or measured with economic indicators, but we can assume, at least for our countries, the existence of some positive relationship between spending per student (on teachers, facilities, equipment, etc.) and the quality of teaching. as far as the offer is concerned.